2018 Korean society of hypertension guidelines for the management of hypertension: part III-hypertension in special situations - Kwang-il Kim; Sang-Hyun Ihm; Gheun-Ho Kim; Hyeon Chang Kim; Ju Han Kim; Hae-Young Lee; Jang Hoon Lee; Jong-Moo Park; Sungha Park; Wook Bum Pyun; Jinho Shin; Shung Chull Chae (BMC, 2019)
Abstract Treatment of hypertension improves cardiovascular, renal, and cerebrovascular outcomes. However, the benefit of treatment may be different according to the patients' characteristics. Additionally, the target blood pressure or initial drug choice should be customized according to the special conditions of the hypertensive patients. In this part III, we reviewed previous data and presented recommendations for some special populations such as diabetes mellitus, chronic kidney disease, elderly people, and cardio-cerebrovascular disease.